1974
DOI: 10.1103/physrevb.9.1077
|View full text |Cite
|
Sign up to set email alerts
|

Phonon behavior and disorder mechanism in NaClO3

Abstract: The dielectric constant of sodium chlorate has been analyzed on the basis of a Mason-Debye-type relaxation formula. A consistent description of the temperature dependence of the phonon structure and the dielectric-constant behavior as a function of frequency and temperature is obtained for this nonferroelectric order-disorder crystal. The fluctuation meccan»nm responsible for the dielectric relaxation behavior is identified as that of the apex reversal of the chlorate ion as one approaches the transition tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1977
1977
1989
1989

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“….Na vector coinciding with the C3 axis of the P213 unit One is therefore forced to conclude that evidence from interatomic distances in crystals is not likely to lead to meaningful estimates of the effective radius of a LP, since accidents of packing appear generally to obscure whatever systematic effects may arise from the effective size of the LP. shortest O...Cl distance in ~MSOHS; allowing 0 : 4 A for the 4~h e frequency and temperature dependence of the dielectric size difference between and leaves a residue of 0 '4 A' constant of NaC103 have been interpreted (53) as involving inversion Funher, the shortest 0' ''1 For personal use only. Effective volume.…”
Section: Spatial Extension Of the Lp In Crystalsmentioning
confidence: 99%
“….Na vector coinciding with the C3 axis of the P213 unit One is therefore forced to conclude that evidence from interatomic distances in crystals is not likely to lead to meaningful estimates of the effective radius of a LP, since accidents of packing appear generally to obscure whatever systematic effects may arise from the effective size of the LP. shortest O...Cl distance in ~MSOHS; allowing 0 : 4 A for the 4~h e frequency and temperature dependence of the dielectric size difference between and leaves a residue of 0 '4 A' constant of NaC103 have been interpreted (53) as involving inversion Funher, the shortest 0' ''1 For personal use only. Effective volume.…”
Section: Spatial Extension Of the Lp In Crystalsmentioning
confidence: 99%
“…This was suggested by Rao et al [4] from an analysis of the low-frequency part of the dielectric constant, which could not be explained by regular phonon contributions alone. The deviation was interpreted in terms of a Debyelike relaxational process, which they speculate might be due to a double-well disordering of C1-atoms.…”
Section: Introductionmentioning
confidence: 78%
“…The dashed line is only a guide to the eye 250 K. Above this temperature they broaden and merge, and the broad peak moves to lower frequencies. However, this behaviour can only qualitatively explain the temperature dependence of the dielectric constant [4]. The present study was undertaken because data for the acoustic phonons for NaC10, have not been reported.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations